Entrepreneurial marketing: The missing link in social enterprise studies - Mohammad Asgari Ghods (Journal of Global Entrepreneurship Research, 2019)
In spite of the recurrent emphasis on the importance of social enterprise (SEs) in the entrepreneurship literature, there has never been a research conducted on the marketing approaches for a social enterprise. The focus of this article is on the entrepreneurial marketing (EM) aspects in social enterprises by reviewing more than 170 articles that had to do with SEs and marketing including marketing for non-profits, SE management, financing SEs, social marketing, services marketing, relationship marketing, and entrepreneurial marketing. The analysis of the review revealed that a social enterprise can enjoy the elements of entrepreneurial marketing in four areas: first, in competing in the market; second, in its endeavors to attract finance to its structure; third, in employing volunteers; and fourth, in presenting its services or product to its target audience. The relative domains are finally proposed in a model of entrepreneurial marketing in social enterprises which shows that EM in SEs is not a single-dimension phenomena but is rather a multipurpose tool in service of any social enterprise to be enjoyed in the four aforementioned areas.
Keywords: 650; Marketing for social enterprises; Entrepreneurial marketing; Marketing; Social enterprises; Ghods